Does Milton Friedman Support a Vigorous Business Ethics? - Cosans, Christopher (Journal of business ethics, 2009)
This paper explores the level of obligation called for by Milton Friedman’s classic essay “The Social Responsibility of Business is to Increase Profits.” Several scholars have argued that Friedman asserts that businesses have no or minimal social duties beyond compliance with the law. This paper argues that this reading of Friedman does not give adequate weight to some claims that he makes and to their logical extensions. Throughout his article, Friedman emphasizes the values of freedom, respect for law, and duty. The principle that a business professional should not infringe upon the liberty of other members of society can be used by business ethicists to ground a vigorous line of ethical analysis. Any practice, which has a negative externality that requires another party to take a significant loss without consent or compensation, can be seen as unethical. With Friedman’s framework, we can see how ethics can be seen as arising from the nature of business practice itself. Business involves an ethics in which we consider, work with, and respect strangers who are outside of traditional in-groups.